PENGAPLIKASIAN TEKNOLOGI PENGERINGAN KAYU SKALA MIKRO di UD. IKA JATI JOMBANG - Ramli Ramadhan; Galit Gatut Prakosa (Future Science, 2020)
Improving the quality of teak branches using micro-scale wood drying techniques is one that UD partners need. Ika Jati. This is because teak branches are considered to have lower economic value than the main trunk. In addition, the quality of branch wood is not physically strong so that the resistance to wood destroying organisms is lower. But now teak branches are starting to be used for various innovations such as blocks for mosaic walls, table mats, chair mats and handicrafts. Through community service (PM), assistance is provided on how to design, apply and find out the effectiveness of using micro-scale wood drying technology. The method used is to design a dryer, oven the branches. The results show that the micro-scale oven is effective and efficient for partners. This is due to the efficiency of the shorter time, does not require a lot of wood fuel and can adjust consumer demand if the demand is relatively small.